Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation